Preventing 'same-day' cancellations in elective urological surgery: Are different strategies needed for inpatient, day case and procedural admissions?. (September 2015) - O'Dwyer, AJ; Pridgeon, S; Green, JSA
Background: Late surgical cancellations adversely impact patients and efficient use of hospital resources. Non-clinical reasons have a cancellation rate of 0.77%, but when including clinical reasons this rate rises to 13%–15%. 1–4 Objectives: The objectives of this article are to identify reasons for cancellations of elective urological procedures at a single centre across different procedure types and to make recommendations for prevention. Methods: Rates and reasons for late cancellation of urological surgery were retrospectively audited for the period April 2009 to April 2012. For each cancellation, reasons were classified: Patient-related, Facility-related, Work-up, Change in medical condition, Process-related, Miscellaneous. Results: During the study period, 9039 elective operations were reviewed to find 2804 cancellations: 580, 450, 1774 (rates = 15.6%, 21.7% and 29.3%) for inpatient, day case and procedure-room cases, respectively. Thirty per cent of inpatient cancellations were due to process-related factors, and 35% due to change in medical condition, of which 78% were urinary tract infection (UTI). Patient-related factors accounted for the majority (52%) of day case and procedural cancellations. Conclusions: Causes for cancellations vary according to procedure type, suggesting tailored strategies are needed for prevention. Change in medical condition caused similar rates of cancellation across procedure type (35%, 28% and 25%). Inpatient procedures were prone to process-related cancellations especially over-run theatre sessions. Patient surveys and reminders closer to time of operation, improvements in preoperative UTI detection and treatment and further process mapping is recommended to identify exact reasons behind and decrease cancellations.